ANALISIS PEMELIHARAAN SALURAN DISTRIBUSI 20 KV DALAM KEADAAN BERTEGANGAN DI RAYON KUTA - Wahyunitya S, I N Tidi; Maharta Pemayun, A A Gede; Ibi Weking, Antonius (Jurnal SPEKTRUM, 2017)
Power outages for maintenance work may result in the customers’ losses and for the State Owned-Power Plant (PLN) itself. The losses are the discontinuity of power distribution or loss of supply for which PLN receives customer complaints or financially penalized. Therefore, a live-line maintenance (PDKB) is needed to overcome the loss of supply. Before doing the live-line maintenance, investment feasibility studies need to be done on the tools for live-line maintenance from the economical aspects. The method used in this research is the Net Present Value (NPV), Internal Rate Of Return (IRR) and Net Benefit Cost Ratio (NET B / C), so it can be determined the total value for the rate of profit through the live-line maintenance . The live-line maintenance (PDKB) at PT PLN (Persero) of Kuta region can save money of Rp.8.941.763.694 kWh / year. Sistem Average Interruption Duration Index (SAIDI) that can be saved was 991.812243 minutes / customer, for System Average Interruption Frequency Index (SAIFI) was 14.60000046 times / customers, Net Present Value was positive of Rp.27.347.312.169, Internal Rate Of Return obtained was 18.111%, while Net Benefit Cost Ratio was 6.462 greater than 1. Therefore, the live-line maintenance work is technically and economically feasible.